Death in Jewish Life Burial and Mourning Customs Among Jews of Europe and Nearby Communities - Reif, Stefan C.; Lehnardt, Andreas (Rethinking Diaspora, 2014)
This volume examines in inter-disciplinary perspective the degree to which the medieval Ashkenazi were innovative in the area of communal activity surrounding burial and mourning customs. The topics cover liturgical poetry as well as statutory prayers confessions, final testimonies and acts of charity funeral and mourning rites the influences of the surrounding non-Jewish the effects of major acts of persecution.